1993
DOI: 10.1111/j.1365-2958.1993.tb00962.x
|View full text |Cite
|
Sign up to set email alerts
|

Crystalline bacterial cell surface layers

Abstract: Crystalline arrays of proteinaceous subunits forming surface layers (S-layers) are one of the most commonly observed prokaryotic cell envelope structures. They are ubiquitous amongst Gram-positive and Gram-negative archeaobacteria and eubacteria and, if present, account for the major protein species produced by the cells. S-layers can provide organisms with a selection advantage by providing various functions including protective coats, molecular sieves, ion traps and structures involved in cell surface intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
170
0
5

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 192 publications
(176 citation statements)
references
References 57 publications
1
170
0
5
Order By: Relevance
“…They found that the S-layer proteins of B. sphaericus are responsible for the bioremediation of uranium from aqueous environments. The S-layer is a porous layer consisting of identical proteins which surround the bacterial cell and can contribute up to 15% of the total cell protein content ( Figure 3) [36]. Sleytr et al found that S-layers are approximately 5-15 nm thick and consist of pores with a size range of 2-6 nm [36].…”
Section: Nanoparticle Synthesis By Bacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the S-layer proteins of B. sphaericus are responsible for the bioremediation of uranium from aqueous environments. The S-layer is a porous layer consisting of identical proteins which surround the bacterial cell and can contribute up to 15% of the total cell protein content ( Figure 3) [36]. Sleytr et al found that S-layers are approximately 5-15 nm thick and consist of pores with a size range of 2-6 nm [36].…”
Section: Nanoparticle Synthesis By Bacteriamentioning
confidence: 99%
“…The S-layer is a porous layer consisting of identical proteins which surround the bacterial cell and can contribute up to 15% of the total cell protein content ( Figure 3) [36]. Sleytr et al found that S-layers are approximately 5-15 nm thick and consist of pores with a size range of 2-6 nm [36]. It is this layer that was proposed by Pollman et al to be responsible for the binding of heavy metals, such as U at up to 20 mg of U per gram of protein, and they suggested that binding was via the carboxyl and phosphate groups of the S-layer resulting in bioaccumulation.…”
Section: Nanoparticle Synthesis By Bacteriamentioning
confidence: 99%
“…Adhesion properties of Bacillus cereus CH protective lattice (Egelseer et al, 1995;Sleytr et al, 1993). Around 18 species of Bacillus have been shown to possess S-layers and, in B. cereus, S-layer proteins have been linked to the adhesion to the host in vegetative cells and to the resistance to phagocytosis (Kotiranta et al, 2000;Sidhu & Olsen, 1997).…”
Section: Identification Of Proteins Associated With the B Cereus Ch mentioning
confidence: 99%
“…ra Sleytr & Sa! ra, 1997 ;Sleytr et al, 1993Sleytr et al, , 1999. Slayers exhibit oblique (p1, p2), square (p4) or hexagonal (p3, p6) lattice symmetry and they are composed of identical protein or glycoprotein subunits.…”
Section: Introductionmentioning
confidence: 99%